Thermomechanical Performance of the Offset Crankshaft Heat Engine Driven by TiNiCu Shape Memory Alloys - Kasama Srirussamee; Anak Khantachawana; Bunheng Hok; Aphinan Phukaoluan (My University, 2021)
Geothermal hot springs are among the alternative clean energy sources to the fossil fuels for mitigating the current global warming crisis.However, the accessible geothermal water at the surface was mostly at low temperature, which impairs the practicality of harvesting these energy.Shape memory alloys (SMAs), which deform through the increased temperature, were adapted into the rotating mechanism as the actuators with the aims to convert the low-temperature heat into the mechanical work.This study utilized the helical spring-shaped TiNiCu SMAs as the actuators for the offset crankshaft heat engine.Performance of this engine was evaluated using rope brake dynamometer, by which the rotational speed, torque, and power were measured at the water temperature from 55-85°C.The results show that the engine performance increased with increasing water temperature and was dependent on the crankshaft arrangement.The offset angle of 30° was found to be optimal in this study with maximum torque of more than 5.8 N•m and maximum power of 3.9 W at 15.7 rpm when operating at water temperature of 85°C.This study shows that the heat engine driven by TiNiCu SMAs could harvest low-temperature energy from the geothermal hot springs with the maximum observable efficiency of around 1.4%.
Keywords: Shape Memory Alloy Transformations